If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 93 + -1(6x + -10) = 6(x + 3) + x Reorder the terms: 93 + -1(-10 + 6x) = 6(x + 3) + x 93 + (-10 * -1 + 6x * -1) = 6(x + 3) + x 93 + (10 + -6x) = 6(x + 3) + x Combine like terms: 93 + 10 = 103 103 + -6x = 6(x + 3) + x Reorder the terms: 103 + -6x = 6(3 + x) + x 103 + -6x = (3 * 6 + x * 6) + x 103 + -6x = (18 + 6x) + x Combine like terms: 6x + x = 7x 103 + -6x = 18 + 7x Solving 103 + -6x = 18 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 103 + -6x + -7x = 18 + 7x + -7x Combine like terms: -6x + -7x = -13x 103 + -13x = 18 + 7x + -7x Combine like terms: 7x + -7x = 0 103 + -13x = 18 + 0 103 + -13x = 18 Add '-103' to each side of the equation. 103 + -103 + -13x = 18 + -103 Combine like terms: 103 + -103 = 0 0 + -13x = 18 + -103 -13x = 18 + -103 Combine like terms: 18 + -103 = -85 -13x = -85 Divide each side by '-13'. x = 6.538461538 Simplifying x = 6.538461538
| 14-1=5 | | 12z^2-28z+11= | | f(x)=9x^2+3x+3 | | 5x+2x-4=45 | | 5x^2+6x+1=42 | | -25(10+x)=25x+250 | | 0.25+0.05n=0.05+0.1n | | 5x-2(3x-7)=3(2x-9)+7x | | 4+3(x+9)=22 | | 30=9X+2-5X | | -2w+48=7(w+3) | | 18=x+125 | | 5y^2+75y-170= | | 0.55p=9.9 | | -2y^2-6y=-2 | | (2sinx-1)(cosx+1)= | | 18=9x+2-5x | | 0.4x+0.8=3.6 | | 240x+0.25=387.50 | | 5x=21x+28 | | 2.4=6.5+y | | 34+(-3)(12)= | | 3x-5(x-4)=-8+4x-20 | | 2x-15+4x=4(3x-6)+6 | | 8x+3=8x-4x | | 11-y=6 | | 4g+2(-8+5g)=1-g | | 2x+5=7z+6 | | (-3)(-4)+7= | | 20-6(2x-3)=-4 | | 3(x-10)=90 | | 4(x-5)-5=6x+7*4-4x |